Perancangan User Experience Aplikasi Manajemen Usaha Sadap Pinus pada KTH Enggal Mulya Lestari Ngrayun Ponorogo - Meita Purnayasari; Fais Al Huda; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Sustainable Community-Based Forest Management (PHBML) is a form of commitment by the Enggal Mulya Lestari Forest Farmers Group (KTH), Mrayan Village, Ngrayun District, Ponorogo Regency under the auspices of the Forest Service Branch (CDK) in the Pacitan area of ​​the East Java Province Forest Service. The steps taken in implementing this commitment are to manage community forests in the form of deposits from tapping pine trees, data on land-owning farmers, data on Forest Farmer Group (KTH) employees and income transaction data for farmers and for Forest Farmer Groups (KTH) which in turn Initially the recording was done in print to utilize digital media. This study aims to design a user experience for a pine tapping business management application that utilizes methods from Human Centered Design (HCD) for its research flow which aims to design solutions that are designed to suit user needs because it involves users in its design, while for testing it uses usability testing. the results of the testing which took the aspects of effectiveness and efficiency obtained satisfactory results, but from the aspect of user satisfaction using the questionnaire from the System Usability Scale (SUS) the results were unsatisfactory so it was necessary to improve the solution design for further implementation